Selected problems of environmental education in a holistic view of sustainable development - Sandner, Jan (Studia Ecologiae et Bioethicae, 2010)
The article is an attempt to define the problems of holistic thinking in terms of environmental education. Development of appropriate methodology in this matter should ensure a better understanding of the environment, but also indicate the mistakes made so far in the process of environmental education. All these activities should create a new quality in the issues of land management. This should lead to more effective crisis management in the natural environment on the ideals of sustainable development. Preparation of appropriate methods of teaching about the resources of the natural environment, consistent with the idea of holistic education, becoming one of the most important goals we are currently facing. Achieving these objectives is necessary in light of the tasks that are put in the idea of sustainable development. Develop a unified methodology for the holistic environmental education, environmental philosophy and environmental ethics should ultimately affect not only the state of knowledge regarding these issues but also create future substantive grounds for studies of the process of pro-environmental attitudes.